Clinical characteristics and outcomes of children with WAGR syndrome and Wilms tumor and/or nephroblastomatosis: The 30-year SIOP-RTSG experience - Hol, Janna A.; Jongmans, Marjolijn C. J.; Sudour-Bonnange, Helene; Ramirez-Villar, Gema L.; Chowdhury, Tanzina; Rechnitzer, Catherine; Pal, Niklas; Schleiermacher, Gudrun; Karow, Axel; Kuiper, Roland P.; De Camargo, Beatriz; Avcin, Simona; et al. (Cancer, 2020)
Background WAGR syndrome (Wilms tumor, aniridia, genitourinary anomalies, and range of developmental delays) is a rare contiguous gene deletion syndrome with a 45% to 60% risk of developing Wilms tumor (WT). Currently, surveillance and treatment recommendations are based on limited evidence.
CRIS-Team WoS Importer:2020-11-20